Changes in the Specific Gravity of Small Yellow Croaker (Larimichthys polyactis) During Early Life History - Hyung-Jin Ahn; In-Uk Hwang; Seung-Jun Lee; Kyung-Nam Han (Ocean Science Journal, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Blood culture bottles meet the operating room: enhancing the diagnostic accuracy of infectious spondylitis through open microsurgical biopsy and intraoperative inoculation - Kyung Joon Kim; Dong Hwan Kim; Kyoung Hyup Nam; Byung Kwan Choi; Seungjin Lim; Jongyoun Yi; In Ho Han; Kye-Hyung Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Mortality and Physiological Responses with Regard to the Surf Clam, Mactra quadrangularis, Exposed to Chlorine - Seon-Sik Lee; Hyung-Jin Ahn; In-Uk Hwang; Eun Kim; Kyung-Nam Han (Ocean Science Journal, 2021)

Cadmium Accumulation and mRNA Expression Associated with Detoxification in Various Organs of Black Seabream (Acanthopagrus schlegelii) Exposed to Cadmium-contaminated Diet - Won-Jun Yeo; Hyung-Jin Ahn; In-Uk Hwang; Keon-ho Lee; Kyung-Nam Han (Ocean Science Journal, 2020)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

2-(4-{2-[(phenylthio)acetyl]carbonohydrazonoyl}phenoxy)acetamide as a new lead compound for management of allergic rhinitis - Hee-Yun Kim; Sun-Young Nam; Jae-Bum Jang; Youngjin Choi; In-Cheol Kang; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2016)

Production of transgenic spermatozoa by lentiviral transduction and transplantation of porcine spermatogonial stem cells - Byung-Gak Kim; Yong-Hee Kim; Yong-An Lee; Bang-Jin Kim; Ki-Jung Kim; Sang-Eun Jung; Hak-Jae Chung; Seongsoo Hwang; Sun-Ho Choi; Myung Jick Kim; Dong-Hoon Kim; In Cheul Kim; et al. (Tissue Engineering and Regenerative Medicine, 2014)

Serum Zinc Concentration Is Inversely Associated with Insulin Resistance but Not Related with Metabolic Syndrome in Nondiabetic Korean Adults - Bang-In Ahn; Moon Jong Kim; Hyung Suk Koo; Namkyung Seo; Nam-Seok Joo; Young-Sang Kim (Biological Trace Element Research, 2014)

Triterpenoids from Fragaria ananassa calyx and their inhibitory effects on melanogenesis in B16-F10 mouse melanoma cells - Na-Young Song; Jin-Gyeong Cho; Dongmoon Im; Dae-Young Lee; Qian Wu; Woo-Duck Seo; Hee Cheol Kang; Youn-Hyung Lee; Nam-In Baek (Natural Product Research, 2013)

Melatonin improves adriamycin-induced hepatic oxidative damage in rats - In-Chul Lee; Sung-Hwan Kim; Hyung-Seon Baek; Changjong Moon; Chun-Sik Bae; Sung-Ho Kim; Won-Kee Yun; Ki-Hoan Nam; Hyoung-Chin Kim; Jong-Choon Kim (Molecular & Cellular Toxicology, 2013)

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus - Hae-Mi Nam; Kyung-Sil Chae; Young-Jo Song; Nak-Hyung Lee; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; Sang-Moo Kang; Min-Chul Kim; In-Soo Choi (Archives of Virology, 2013)

An efficient selection and regeneration protocol for Agrobacterium-mediated transformation of oriental melon (Cucumis melo L. var. makuwa) - Jun Young Choi; Jeong Sheop Shin; Young Soo Chung; Nam-In Hyung (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

A method for detecting significant genomic regions associated with oral squamous cell carcinoma using aCGH - Ki-Yeol Kim; Jin Kim; Hyung Jun Kim; Woong Nam; In-Ho Cha (Medical & Biological Engineering & Computing, 2010)

Simultaneous suppression of three genes related to brassinosteroid (BR) biosynthesis altered campesterol and BR contents, and led to a dwarf phenotype in Arabidopsis thaliana - Ho Yong Chung; Shozo Fujioka; Sunghwa Choe; Soyoun Lee; Youn Hyung Lee; Nam In Baek; In Sik Chung (Plant Cell Reports, 2010)

Isolation and promoter analysis of anther-specific genes encoding putative arabinogalactan proteins in Malus × domestica - Yeon-Ok Choi; Sung-Soo Kim; Sanghyeob Lee; Sunggil Kim; Gi-Bo Yoon; Hyojeong Kim; Young-Pyo Lee; Gyung-Hee Yu; Nam-In Hyung; Soon-Kee Sung (Plant Cell Reports, 2010)

Enhanced fungal resistance in Arabidopsis expressing wild rice PR-3 (OgChitIVa) encoding chitinase class IV - Jung-Hun Pak; Eun-Sook Chung; Sang-Hyun Shin; Eun-Hee Jeon; Mi-Jin Kim; Hye-Young Lee; Ji-Ung Jeung; Nam-In Hyung; Jai-Heon Lee; Young-Soo Chung (Plant Biotechnology Reports, 2009)

Constitutive expression of two pathogenesis-related genes in tomato plants enhanced resistance to oomycete pathogen Phytophthora capsici - Sujon Sarowar; Young Jin Kim; Eui Nam Kim; Ki Deok Kim; Jun Young Choi; Nam In Hyung; Jeong Sheop Shin (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Isolation and characterization of a myo-inositol 1-phosphate synthase cDNA from developing sesame (Sesamum indicum L.) seeds: functional and differential expression, and salt-induced transcription during germination - Jae-An Chun; Un-Ho Jin; Jin-Woo Lee; Young-Byung Yi; Nam-In Hyung; Myung-Hwa Kang; Jae-Ho Pyee; Mi Suh; Churl-Whan Kang; Hong-Yeol Seo; Shin-Woo Lee; Chung-Han Chung (Planta, 2003)

Microarray analysis of piceatannol-induced changes in gene expression in human gastric cancer cells - Dooil Jeoung; Seong-Jun Oh; Seongeun Lee; Myungin Baek; Youn-Hyung Lee; Nam-In Baek; Hae-Yeong Kim (Biotechnology Letters, 2002)

Characterization of PPO (polyphenol oxidase) cDNA in sweet persimmon (Diospyros kaki) - Sung Chul Bahn; Young Soo Chung; Jeong Sheop Shin; Chang Hoo Lee; Nam In Hyung (Journal of Plant Biology, 1999)